Soil Nutrient Content Analysis of Newly-Increased Farmland in the Process of Land Consolidation In Shaanxi Province, China (Bangladesh Journal of Botany, 2023)
The aim of this study is to analyze the characteristics of soil nutrient content of newly increased cultivated land in land consolidation, and identify the main factors affecting the productivity of newly increased cultivated land. The soil samples of 101 newly added cultivated land in northern, central and southern Shaanxi were collected, and their pH value, organic matter, total nitrogen, available phosphorus and available potassium contents were measured to analyze the soil nutrient status. The results indicated that the contents of soil organic matter, total nitrogen, available phosphorus and available potassium in the newly increased cultivated land were 0.21~23.63 g/kg, 0.20~8.27 g/kg, 2.34~34.16 mg/kg and 51~220 mg/kg, respectively. Compared with the nutrient grading standard of the second national soil survey, the content of soil nutrients in the newly increased cultivated land was relatively low, basically at the level of four to six. It was also revealed that Tte soil nutrient content of newly increased cultivated land in Shaanxi Province is greatly affected by the original land use types in northern Shaanxi and Guanzhong, and the soil nutrient difference in southern Shaanxi is mainly caused by the random changes among plots in the same region; The variance test showed that there were significant differences in soil pH organic matter and available potassium at 0.05 level, but no significant differences in soil total nitrogen and available phosphorus at 0.05 level. (3) It can be seen from the correlation analysis that among the nutrient indicators of the newly increased farmland in Shaanxi, pH organic matter has a significant negative correlation, and organic matter available potassium and available phosphorus available potassium have a very significant correlation. The correlation between soil nutrients in the newly increased farmland is weak, and the coordination between nutrients is poor. The low content of organic matter in soil is the main reason for low fertility. In the later stage of utilization, it is necessary to promote straw returning technology through the reasonable application of organic inorganic fertilizer and the application of soil testing formula fertilization technology, so as to finally realize the stable and high yield of newly added farmland.Bangladesh J. Bot. 51(4): 1017-1028, 2022 (December) Special